Fascicle length of leg muscles is greater in sprinters than distance runners - Abe, T.; Kumagaj, K.; Brechue, W. F. (Medicine & Science in Sports & Exercise, 2000)
Purpose: The purpose of this study was to compare architectural characteristics of leg muscles of sprinters and distance runners. Methods: Skeletal muscle architectural characteristics were studied in 23 elite male 100-m sprinters (SPR, 10.0-10.9 s for 100 m), 24 elite male distance runners (DR, 13.5-14.5 min for 5000 m), and 24 untrained male controls. Fascicle pennation angle and isolated muscle thickness of the vastus lateralis and gastrocnemius medialis and lateralis muscles were measured in vivo by ultrasound, and fascicle length was estimated. Results: Standing height and upper and lower limb lengths were similar among the groups. Body weight was significantly greater in SPR than in either DR or controls, which were similar. Muscle thickness of the vastus lateralis and gastrocnemius medialis and lateralis muscles was significantly greater in SPR than in either DR or controls, which were similar. In all muscles, pennation angle was similar between SPR and controls, but less than DR. Fascicle length of the vastus lateralis muscle (absolute and relative to limb length) was greatest in SPR and least in DR with control values being between the athlete groups. Fascicle length of the gastrocnemius medialis muscle (absolute and relative to limb length) was greater in SPR than in either DR or controls, which were similar. Fascicle length of the gastrocnemius lateralis muscle (absolute and relative to limb length) was significantly greater in SPR than DR. Absolute fascicle length in gastrocnemius lateralis muscle was similar between DR and controls; however, relative to limb length DR was significantly less. Conclusion: Greater fascicle length and lesser pennation angle observed in leg muscles of SPR, compared with DR, would appear to favor shortening velocity as required for greater running speed.